Synthesis of Polyaniline/Zn Bismuthate Nanocomposites and Sensitive Formaldehyde Sensing Performance - Pei, Lizhai; Qiu, Fanglv; Ma, Yue; Lin, Feifei; Fan, Chuangang; Ling, Xianzhang (Current Nanoscience, 2019)
Background: Formaldehyde belongs to important pollutant and is usually found in liquid environment, such as juices, beer, cleaning products and biological fluid of the human. The electrochemical sensors using glassy carbon electrode (GCE) modified with polyaniline/Zn bismuthate nanocomposites can effectively detect formaldehyde with broad linear range and good reproducibility. Methods: Polyaniline/Zn bismuthate nanocomposites were prepared by in-situ aniline polymerizing route in aqueous solution. The structure and morphologies of the nanocomposites were analyzed by X-ray diffraction (XRD) and transmission electron microscopy. The electrochemical performance for formaldehyde detection has been investigated by cyclic voltammetry (CV) method using polyaniline/ Zn bismuthate nanocomposites modified GCE. Results: XRD shows that ZnBi38O58 phase exists in the nanocomposites. Amorphous polyaniline attaches to the surface of the Zn bismuthate nanorods. The 20wt.% polyaniline/Zn bismuthate nanocomposites modified GCE shows an irreversible cyclic voltammetry (CV) peak at –0.06 V. The peak current increases sharply with increased scan rate, formaldehyde concentration and acidity. The electrochemical response dependences including the linear range, detection limit were analyzed. 20wt.% polyaniline/Zn bismuthate nanocomposites modified GCE shows low detection limit of 0.0095 μM and wide linear range of 0.00001-2 mM. The detection limit for formaldehyde decreases from 0.028 μM to 0.0075 μM with the increase in the polyaniline content from 10wt.% to 40wt.%. Conclusion: The low detection limit and wide linear range make the nanocomposites modified GCE valuable for sensor application. Polyaniline/Zn bismuthate nanocomposites are identified as the prominent electrode materials for sensitive formaldehyde detection.
Keywords: Zn bismuthate nanorods